2019
DOI: 10.1111/1365-2435.13284
|View full text |Cite
|
Sign up to set email alerts
|

Sink limitation of plant growth determines tree line in the arid Himalayas

Abstract: Understanding what determines the high elevation limits of trees is crucial for predicting how tree lines may shift in response to climate change. Tree line formation is commonly explained by a low‐temperature restriction of meristematic activity (sink limitation) rather than carbon assimilation (source limitation). In arid mountains, however, trees face simultaneously low temperature and drought, both potentially restricting their growth and thus setting range limits. However, the mechanisms of tree line form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Starch greatly increased at mid‐high elevations where, in the same sample areas, a strong reduction of V. myrtillus also occurred (Boscutti et al., ). The NSC pattern observed in V. myrtillus shows the same trend already observed in Himalayan populations of Myricaria elegans (Dolezal et al., ), although V. myrtillus population evidenced a stronger effect of altitude. Moreover, similar to what has been described for the vegetative organs of bilberry collected at different latitudes (Pakonen et al., ), our results revealed that when sucrose decreased, products of its hydrolysis (fructose and glucose) increased.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Starch greatly increased at mid‐high elevations where, in the same sample areas, a strong reduction of V. myrtillus also occurred (Boscutti et al., ). The NSC pattern observed in V. myrtillus shows the same trend already observed in Himalayan populations of Myricaria elegans (Dolezal et al., ), although V. myrtillus population evidenced a stronger effect of altitude. Moreover, similar to what has been described for the vegetative organs of bilberry collected at different latitudes (Pakonen et al., ), our results revealed that when sucrose decreased, products of its hydrolysis (fructose and glucose) increased.…”
Section: Discussionsupporting
confidence: 83%
“…It is widely recognized that elevation affects plant growth and physiology by generating more severe environmental conditions, namely, increased exposure to low temperatures (Körner, ; Schulze et al., ; von Arx et al., ), and consequent reduction of the growing period also due to prolonged snow cover (Körner, ; Jonas et al., ). Nonstructural carbohydrates have been shown to respond to environmental stress associated with altitude (Fajardo et al., ; Dolezal et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the studied alpine and subalpine plants were controlled by summer (mostly July–August) temperatures during the colder 1970s–1980s period, they have become dependent on spring (March) temperature and summer (current July and previous September) precipitation during the warmer 1990s–2000s period. The reduced growth with the occurrence of warm and dry weather during the previous September may reflect increased plant respiration and reduced carbohydrate reserve, with both factors causing fewer assimilates to be stored throughout the rhizome, thus resulting in a lower growth potential in the following vegetation season (Dolezal et al ., 2019). The increased sensitivity to summer precipitation is intriguing because R. alpinus is usually bound to sites with high groundwater levels (Stachurska‐Swakoń, 2009) and is even capable of tolerating temporary waterlogging and low soil oxygen levels through the formation of conspicuous intercellular spaces in the rhizome cortex (schizogenous aerenchyma, Schweingruber et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the decrease in temperature with increasing elevations has been recognized as a major reason for treeline formation, and the mechanism by which low temperature affects the growth of treeline trees is unclear. The concordance of this treeline isotherm suggests a common low-temperature effect on plant metabolism, either related to carbon (C) gain (source activity; photosynthesis) or sink activity (tissues formation; meristems) [4].…”
Section: Introductionmentioning
confidence: 86%